1999
DOI: 10.1200/jco.1999.17.9.2762
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Trial of Temozolomide in Patients With Anaplastic Astrocytoma or Anaplastic Oligoastrocytoma at First Relapse

Abstract: Temozolomide demonstrated good single-agent activity, an acceptable safety profile, and documented HQL benefits in patients with recurrent AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
403
6
11

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 700 publications
(436 citation statements)
references
References 33 publications
16
403
6
11
Order By: Relevance
“…TMZ has shown efficacy in primary brain tumours and metastatic melanoma in phase II trials (Bleehen et al, 1995;Yung et al, 1999) However, in a phase III trial, it was not found to be superior to DTIC (Middleton et al, 2000). In our study, an overall response rate of 31% (24 out of 74 patients) was achieved with a 1-year survival of 41% and a median survival of 252 days.…”
Section: Discussioncontrasting
confidence: 54%
“…TMZ has shown efficacy in primary brain tumours and metastatic melanoma in phase II trials (Bleehen et al, 1995;Yung et al, 1999) However, in a phase III trial, it was not found to be superior to DTIC (Middleton et al, 2000). In our study, an overall response rate of 31% (24 out of 74 patients) was achieved with a 1-year survival of 41% and a median survival of 252 days.…”
Section: Discussioncontrasting
confidence: 54%
“…17 The cells treated with or without TMZ (100 mM) for 72 h were harvested by trypsinization, washed twice with PBS and fixed with ice-cold glutaraldehyde (3% in 0.1 M cacodylate buffer, pH 7.4) for 30 min. After washing in PBS the cells were postfixed in OsO 4 and embedded in Epon; 0.1 mm thin sections were stained with uranyl acetate/lead citrate (Fluka) and viewed in a Philips EM 400 electron microscope.…”
Section: Electron Microscopymentioning
confidence: 99%
“…3,4 TMZ has several advantages over other existing alkylating agents because of its unique characteristics. [5][6][7][8] Because TMZ is a small lipophilic molecule with a molecular weight of 194 Da, it can be administered orally and it crosses the blood-brain barrier effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide (TMZ,3,-as-tetrazine-8-carboxamide) is a new oral alkylating agent that has recently demonstrated efficacy in the treatment of malignant gliomas (O'Reilly et al, 1993;Plowman et al, 1994;Friedman et al, 1995Friedman et al, , 2000Yung et al, 1999). The cytotoxicity of TMZ is primarily due to the formation of O 6 -methylguanine in DNA, which mispairs with thymine during the next cycle of DNA replication (Denny et al, 1994;D'Atri et al, 1995).…”
mentioning
confidence: 99%